Optimizing Employee Work Productivity Through Increasing Motivation and Work Experience - Agus Setiadi; Yohanes Sulistyadi; Ramon Hurdawaty (Green Publisher Indonesia, 2025)
This study aims to identify and analyze the effect of work motivation and work experience on employee productivity at Anak Garuda Shop in Batu City. The research was conducted using an explanatory quantitative approach, with a survey method through a questionnaire. The population consisted of 103 employees, using the census method. The data obtained was analyzed by multiple linear regression and classical statistical tests to verify the relationship between variables. The results showed that: (1) work motivation has a positive and significant effect on employee productivity, (2) work experience also has a positive and significant effect on employee productivity, (3) simultaneously, the two variables have a significant influence on employee productivity, with a contribution of 51.4%. Internal motivation factors, such as management communication, and external, such as community recognition, are the main drivers. Meanwhile, work experience, both from tenure in the company and similar fields, is proven to improve the efficiency and quality of employee work. This research recommends relevant training to enhance work experience and a humanistic communication approach to maintain employee motivation.